Analysis of Economies of Scale in Czech Households Based on Different Approaches - Jirková, Michaela; Musil, Petr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The economic situation of households could be evaluated using different approaches. Nevertheless, all methods have to deal with the same fact: economies of scale. The household structure meaning the size and other demographic and economic characteristics of household members should be always taken into account. Economies of scale are represented by the equivalence scale of consumption units. The current international consumption unit scale may not be appropriate as economies of scales might differ among countries. Therefore, the national scale should be estimated. Economies of scale of Czech households and subsequently consumption unit scales are analysed from more perspectives in the paper. An alternative approach to consumption unit scales applied in other countries is based on household expenditures. We have estimated the consumption unit scale within our previous research. Another method that uses utility function is applied in this paper and compared to the previous one. This utility function of households is indirectly measured using subjective data of financial satisfaction. The analysis is based on data from EU_SILC. Consumption units are estimated applying regression. At first the estimation of economies of scale based on expenditures and utility function are provided. Subsequently, the results of estimated consumption unit’s scale are compared also with international scales. Finally, all approaches are compared and the impact on indicators of income or consumption is assessed
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 227-234
Keywords: economies of scale; consumption units; equivalence scale; household expenditures; utility function